An evaluation of crude palm oil (CPO) and tocotrienol rich fraction (TRF) of palm oil as percutaneous permeation enhancers using full-thickness human skin - Singh, Inderjeet; Nair, Rajesh Sreedharan; Gan, Suyin; Cheong, Victor; Morris, Andrew (Taylor & Francis, 2018)
The drawbacks associated with chemical skin permeation enhancers such as skin irritation and toxicity necessitated the research to focus on potential permeation enhancers with a perceived lower toxicity. Crude palm oil (CPO) is obtained by direct compression of the mesocarp of the fruit of the oil palm belonging to the genus Elaeis. In this research, CPO and tocotrienol-rich fraction (TRF) of palm oil were evaluated for the first time as skin permeation enhancers using full-thickness human skin. The in vitro permeation experiments were conducted using excised human skin mounted in static upright ‘Franz-type’ diffusion cells. The drugs selected to evaluate the enhancing effects of these palm oil derivatives were 5-fluorouracil, lidocaine and ibuprofen: compounds covering a wide range of Log p values. It was demonstrated that CPO and TRF were capable of enhancing the percutaneous permeation of drugs across full-thickness human skin in vitro. Both TRF and CPO were shown to significantly enhance the permeation of ibuprofen with flux values of 30.6 µg/cm2 h and 23.0 µg/cm2 h respectively, compared to the control with a flux of 16.2 µg/cm2 h. The outcome of this research opens further scope for investigation on the transdermal penetration enhancement activity of pure compounds derived from palm oil.